Selected aspects of low emission management in the Middle Odra Region1 - Dzikuć Maciej; Dzikuć Maria (Management)
According to the data of the European Environment Agency, due to excessive air pollution about 47 thousand people die prematurely every year in Poland. Although in recent years the level of industrial emissions in Poland has been significantly reduced, it is still a very serious problem of the so-called low emission. The aim of the paper was to determine the most important sources of low emission in the Middle Odra Region and to indicate activities that will optimally limit this problem. The article points out activities that help reduce low emission in the Middle Odra Region, where the problem is also noticeable, despite the lower population density and the lack of highly industrialized areas. Moreover, it pointed to the possible directions of low emission management, the implementation of which may contribute to a significant reduction of low emission in the Middle Odra Region.